2016
DOI: 10.1002/yd.20167
|View full text |Cite
|
Sign up to set email alerts
|

The Intersectionality of Leadership and Service‐Learning: A 21st‐Century Perspective

Abstract: This chapter provides a theoretical orientation to the intersections of the theory and practice of leadership and service-learning. It articulates a set of values to guide leadership educators in their service-learning practice. The authors advocate a critical approach that fosters social justice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…To the point of this issue of New Directions for Student Leadership , service‐learning as both an experience and pedagogy relates in very powerful ways to what leadership educators increasingly advocate (Wagner & Pigza, ). Service and leadership learning offer both process and product when students and community partners engage in “purposeful action that addresses both immediate and/or systemic change issues” (Wagner & Pigza, , p. 6). Community service involvement has been found to contribute to socially responsible leadership across numerous demographic groups (Dugan, Kodama, & Correia, ); when community service is enhanced with service‐learning principles and linked to leadership, there is even greater potential for positive outcomes.…”
Section: What Is Service‐learning?mentioning
confidence: 99%
“…To the point of this issue of New Directions for Student Leadership , service‐learning as both an experience and pedagogy relates in very powerful ways to what leadership educators increasingly advocate (Wagner & Pigza, ). Service and leadership learning offer both process and product when students and community partners engage in “purposeful action that addresses both immediate and/or systemic change issues” (Wagner & Pigza, , p. 6). Community service involvement has been found to contribute to socially responsible leadership across numerous demographic groups (Dugan, Kodama, & Correia, ); when community service is enhanced with service‐learning principles and linked to leadership, there is even greater potential for positive outcomes.…”
Section: What Is Service‐learning?mentioning
confidence: 99%
“…In fairness to the leadership studies educators cited above, they have also called for appropriate preparation and critical reflection. Wagner and Pigza () suggested that outsiders must have “proper training for their service activity, an understanding of the social issue at hand, the local history, the ways that power and politics shape the context, and the cultural awareness necessary to be effective in service” (p. 12). Dugan et al () recognized that leadership education that overemphasizes leader development may simply reproduce the existing social order, as in the cases above, where privileged students from the North gain validation and even education while exploiting, albeit unintentionally, individuals and communities in the Global South.…”
Section: Contextualized Actions Power Analysis and Discourse Critiquementioning
confidence: 99%
“…Such critiques have prompted considerable bodies of scholarship around critical service‐learning (Mitchell, ), postdevelopment studies (Rahnema & Bawtree, ), and alternatives to leadership development that are increasingly focused on community inclusion, social awareness, and variously de‐centering self (Dugan et al, ; Longo & McMillan, ; Wagner & Pigza, ). These approaches gain much of their strength from the importance of intentionality and participation, including de‐centering traditional authorities; yet, in practice they may not do enough to protect vulnerable populations in global engagement programming.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Wagner and Pigza (2016) argue that addressing 21st century problems effectively requires 21st century notions of leadership and social responsibility. With respect to service-learning and social entrepreneurship, the Social Change Model (SCM) of Leadership Development (HERI, 1996) provides a useful theoretical framework that can guide how we prepare students to engage with community partners and other stakeholders.…”
Section: Toward a Unifying Competency-based Framework Of Participatomentioning
confidence: 99%